Simvastatin Toxicity Induces Alteration of Bladder Thickness in Interstitial Cystitis Rat Model - Z K Yusuf; A D I Hasanuddin; M N S Yusuf; M T Posumah; N Ibrahim; R Tianggara (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: Interstitial cystitis (IC) is a chronic inflammatory of the bladder, while statin can increase its risk.Recently, the exact mechanism is yet known. We hypothesizedsimvastatin can induce alteration of bladderthickness.Methods: Twenty-four female Wistar rats were aged 6-8 weeks old were divided into two groups and weretreated with simvastatin 50 mg/kg BW or carboxymethylcellulose 0.5% by oral gavage for 30 days. Each groupwas then equally subdivided into three groups: control, Interstitial Cystitis (IC) day-0, and IC day-3. Either ICor control rat group was induced by intravesical instillation of protamine sulfate or buffered saline respectively.All animals in the control and IC day-0 group were sacrificed and collected for the bladder tissue in less thanthree hours following intravesical treatment, while animals in the IC day-3 group three days after. All collectedtissue was prepared in hematoxylin-eosin staining and measured for the bladder thickness, namely the urothelial,suburothelial, and detrusor layer by image analyzer application.Results: There was no significant difference between the groups receiving simvastatin and placebo in thethickness of the urothelium, suburothelium, and detrusor layers in all rat models, both control, IC0, and IC3 rats(all p values > 0.05). However, the thickness of the urothelium layer was consistently lower in the simvastatingroup than in the placebo group in all rat models.Conclusion: Mechanism of simvastatin toxicity on bladder tissue through urothelial denudation thus may alterthe urothelial barrier function.